2020
DOI: 10.3390/antibiotics9090571
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Adherence in Antibiotic Prescribing to Patients with Respiratory Diseases in Primary Care: Prevalence and Practice Variation

Abstract: Respiratory tract infections (RTIs) account for a large part of antibiotic prescriptions in primary care. However, guidelines advise restrictive antibiotic prescribing for RTIs. Only in certain circumstances, depending on, e.g., comorbidity, are antibiotics indicated. Most studies on guideline adherence do not account for this. We aimed to assess guideline adherence for antibiotic prescribing for RTIs as well as its variation between general practices (GPs), accounting for patient characteristics. We used data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…GPs prescribe antibiotics for a variety of infectious diseases, ranging from respiratory tract infections (RTI) to cellulitis 5–10. However between 44% and 98% of the antibiotic prescriptions for RTIs are classified as inappropriate 11–14. The proportion of inappropriate antibiotic prescriptions for urinary tract infections is estimated at between 3% and 36.5% 15 16.…”
Section: Introductionmentioning
confidence: 99%
“…GPs prescribe antibiotics for a variety of infectious diseases, ranging from respiratory tract infections (RTI) to cellulitis 5–10. However between 44% and 98% of the antibiotic prescriptions for RTIs are classified as inappropriate 11–14. The proportion of inappropriate antibiotic prescriptions for urinary tract infections is estimated at between 3% and 36.5% 15 16.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that, in 2017, Chinese primary healthcare clinicians prescribed antibiotics for nearly half of outpatients with acute bronchitis, which was a lower rate than those in the studies conducted in Italy (73.5%) 13 , US (74%) 14 , Belgium (69.0%) 15 , Spain (58.6%) 16 , Japan (52.8%) 17 , and Netherlands (51.0%) 18 , and was also lower than previous studies in China (77.5–95.2%) 9 , 11 . However, our rate was slightly higher than the rate showed in the study conducted in Swiss (41.5%) 19 .…”
Section: Discussionmentioning
confidence: 54%
“…There are opportunities for outpatient antimicrobial stewardship interventions for acute sinusitis treatment. Identifying reasons for provider nonadherence to antibiotic prescribing guidelines is crucial to design and implement antimicrobial stewardship interventions (Hek et al, 2020). Educational interventions for providers, with a focus on antibiotic stewardship for ARTIs, can play significant role in reducing unnecessary antibiotic prescription for acute sinusitis treatment.…”
Section: Discussionmentioning
confidence: 99%